2014
DOI: 10.1002/ajim.22393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cleaning and disinfecting tasks and product use among hospital occupations

Abstract: Background Healthcare workers have an elevated prevalence of asthma and related symptoms associated with the use of cleaning/disinfecting products. The objective of this study was to identify and characterize cleaning/disinfecting tasks and products used among hospital occupations. Methods Workers from 14 occupations at five hospitals were monitored for 216 shifts, and work tasks and products used were recorded at five-minute intervals. The major chemical constituents of each product were identified from saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 40 publications
(52 reference statements)
4
60
0
Order By: Relevance
“…In a study conducted in 5 U.S. hospitals, cleaning and disinfecting tasks (at least once per shift), were frequent among registered nurses (66%),[9] consistent with our results. Among U.S. hospital workers[6], self-reported exposures to cleaning and disinfecting products during instrument cleaning (42%) and building surface cleaning (78%) were higher than in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a study conducted in 5 U.S. hospitals, cleaning and disinfecting tasks (at least once per shift), were frequent among registered nurses (66%),[9] consistent with our results. Among U.S. hospital workers[6], self-reported exposures to cleaning and disinfecting products during instrument cleaning (42%) and building surface cleaning (78%) were higher than in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…[1,4,6] Several studies have shown associations with onset or symptoms of asthma but little is known about specific agents involved,[2,3,7] which limits the development of disease prevention strategies. [8] Indeed, identifying which specific agents might affect the respiratory health of healthcare workers is challenging,[4,9] partly due to the lack of suitable exposure assessment methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of respiratory illness in healthcare professionals is much higher than that of the general population (Liss et al, 2011;Bakerly et al, 2008), and exposure to multiple chemicals for prolonged periods of time is almost certainly a contributory factor (Saito et al, 2015;Wiszniewska and Walusiak-Skorupa, 2014). There are well-documented reports of occupational asthma attributable to glutaraldehyde, but the prevalence is low ( Vandenplas et al, 2011).…”
Section: Glutaraldehydementioning
confidence: 99%
“…In another study conducted in French hospitals, Gonzalez et al 22 reported that around 75%, 50% and 20% of participants were exposed to quats, chlorinated products/bleach (mainly cleaners) and glutaraldehyde, respectively. In five US hospitals, Saito et al 26 observed that products containing alcohols were the most frequently used by clinical laboratory technicians, certified nursing assistants and registered nurses (58%, 75% and 68% of shifts) for a mean duration of 45 min. For housekeepers, products with alcohol and quats were the most frequently used (>90% of shifts) for a mean duration of 115 min 26…”
Section: Discussionmentioning
confidence: 99%